2017
DOI: 10.1161/jaha.117.007199
|View full text |Cite
|
Sign up to set email alerts
|

Association Between APOL1 Genotypes and Risk of Cardiovascular Disease in MESA (Multi‐Ethnic Study of Atherosclerosis)

Abstract: Background APOL1 genetic variants confer an increased risk for kidney disease. Their associations with cardiovascular disease (CVD) are less certain. We aimed to compare the prevalence of subclinical CVD and incidence of atherosclerotic CVD and heart failure by APOL1 genotypes among self‐identified black participants of MESA (Multi‐Ethnic Study of Atherosclerosis).Methods and ResultsCross‐sectional associations of APOL1 genotypes (high‐risk=2 alleles; low‐risk=0 or 1 allele) with coronary artery calcification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
(139 reference statements)
1
22
0
Order By: Relevance
“…In the Multiethnic Study of Atherosclerosis, the association with overall heart failure was unchanged when adjusting for baseline eGFR or urine albumin excretion. 16 These findings suggest that additional factors account for the APOL1-HFpEF associations. Variants of APOL1 may modulate furosemide-induced diuresis in heart failure.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the Multiethnic Study of Atherosclerosis, the association with overall heart failure was unchanged when adjusting for baseline eGFR or urine albumin excretion. 16 These findings suggest that additional factors account for the APOL1-HFpEF associations. Variants of APOL1 may modulate furosemide-induced diuresis in heart failure.…”
Section: Discussionmentioning
confidence: 89%
“…Supporting our findings, a recent publication from the Multiethnic Study of Atherosclerosis showed an 82% increased hazard of overall heart failure for carriers of high-risk APOL1 variants (95% CI, 1.01-3.28), although the study did not report associations with heart failure subtypes. 16 The diagnosis of HFpEF is based on typical symptoms and signs of heart failure in a patient with normal LVEF as detected by echocardiography. 32 The condition is present in 30% to 50% of all patients with heart failure, and the prevalence is 2-fold higher in older women than older men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The CHS, the JHS, and the Women's Health Initiative cohorts also reported associations between APOL1 kidney risk variants and incident cardiovascular disease, 13,18 whereas the AA-DHS, the AASK, the ARIC study, the MESA, and the SPRINT did not. 10,12,17,21 The JHS and the AA-DHS reported paradoxical protective relationships between APOL1 kidney risk variants with subclinical cardiovascular disease (calcified atherosclerotic plaque), although in the MESA, there was no significant association. 21,29 Results for mortality have been similarly heterogeneous: the APOL1 kidney risk variants were protective in the AA-DHS (additive genetic model), harmful in the CHS (recessive genetic model), and null in the ARIC study (recessive genetic model).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…However, the literature on APOL1 risk variants and cardiovascular disease is mixed, with some studies finding an association of APOL1 risk variants with cardiovascular disease and death and other studies finding null or protective associations. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Methods differed across studies, particularly with respect to the genetic model, and many had limited statistical power because of low numbers of events.…”
mentioning
confidence: 99%